Green synthesis of silver nanoformulation of Scindapsus officinalis as potent anticancer and predicted anticovid alternative: Exploration via experimental and computational methods. (August 2021) - Pathak, Manish; Pathak, Prateek; Khalilullah, Habibullah; Grishina, Maria; Potemkin, Vladimir; Kumar, Vikas; Majee, Rahul; Ramteke, Pramod W.; Abdellattif, Magda H.; Shahbaaz, Mohd; Verma, Amita
Abstract: The current study was focused on the investigation of anticancer activity of Scindapsus Officinalis fruit extract embedded silver nanoparticles ( So -AgNPs) followed by anticovid activity prognosis of major phytocompounds, which participate in nanoformulation synthesis. The synthesis process involved the addition of AgNO3 solution (1 mM) and color change of the extract from light brown to dark, confirmed the formation of silver nanoparticles. Further, the characterization of synthesized So -AgNPs were done using different spectroscopical and microscopical techniques. FTIR spectra of So-AgNPs indicated vibrational peaks of polyphenolic hydroxyl groups, which are responsible for the stabilization of nanoformulation. Others microscopy methods such as SEM, TEM, XRD, and EDX illustrated that the synthesized So-AgNPs consist irregular size, spherical shape and thoroughly dispersed above the plane. Anticancer evaluation illustrated that the So-AgNPs have dose dependent anti-breast and anti-hepatic cancer activity (range of 97.72 ± 0.42–54.86 ± 0.46% cell viability), which were noticed more effective than raw fruit extract of Scindapsus Officinalis . The computational anticovid prediction of major phyto-compound of the extract [which designate as inhibitor 1: ((2R, 3S, 4S, 5R)-2-(hydroxymethyl)-6-(((1S, 5S)-1-methyl-5-(2-methylprop-1-en-1-yl)cyclopent-2-en-1-yl)oxy)tetrahydro-2H-pyran-3, 4, 5-triol)] illustrated moderate tendency to interact with corona main protease enzyme (expected pIC > 6 μM). However, the molecular docking and dynamics studies showed that selected compounds have moderate tendency to interact human dihydrofolate reductase and topoisomerase 1 enzyme. The accomplished approach shows that So -AgNPs with adsorbed phytocompounds on its surface consist valuable experimentally proved anticancer potency and computationally predicted anticovid effect. Thus, the formulation can be used as an alternative to the covid infected cancer population. Graphical abstract: Image 1 Highlights: Green synthesis of Scindapsus Officinalis stabilized silver nanoparticles. So -AgNPs showed significant activity against r cancer cells. SO-AgNPs shows significant specificity and nontoxic effect against two non-cancerous cell lines.